Family size and child migration: Do daughters face greater trade-offs than sons? - HO, Christine (Institutional Knowledge at Singapore Management University, 2024)
We show that, conditional on family size, rural boys and girls are equally likely to migrate with parents in China. Nevertheless, daughters’ migration may still be compromised because they tend to have more siblings in societies with strong son preference, and larger families are more likely to leave all children behind. We find that a one unit increase in sibship size decreases the probability that a daughter migrates by 12.5 percentage points—with stronger effects when migration restrictions are more stringent—but has negligible effects on sons. The results suggest that gender-neutral migration constraints may generate gendered family size trade-offs.